2010
DOI: 10.1074/jbc.m110.170068
|View full text |Cite
|
Sign up to set email alerts
|

Rod phosphodiesterase-6 PDE6A and PDE6B Subunits Are Enzymatically Equivalent

Abstract: Phosphodiesterase-6 (PDE6) is the key effector enzyme of the phototransduction cascade in rods and cones. The catalytic core of rod PDE6 is a unique heterodimer of PDE6A and PDE6B catalytic subunits. The functional significance of rod PDE6 heterodimerization and conserved differences between PDE6AB and cone PDE6C and the individual properties of PDE6A and PDE6B are unknown. To address these outstanding questions, we expressed chimeric homodimeric enzymes, enhanced GFP (EGFP)-PDE6C-A and EGFP-PDE6C-B, containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 43 publications
(50 reference statements)
5
64
0
Order By: Relevance
“…One of the key unresolved questions is how the physiological differences between rods and cones can be correlated with the distinctive properties of their phototransduction proteins. Previous studies have shown that the lower thermal stability of cone pigments is likely to contribute to the lower sensitivity of cones but, once activated, rod and cone pigments can couple equally efficiently to rod or cone transducin (Kefalov et al, 2003(Kefalov et al, , 2005Shi et al, 2005Shi et al, , 2007Fu et al, 2008). Thus, consistent with our previous research (Deng et al, 2009) and other studies (Ma et al, 2001), the signaling properties of rod and cone transducin ␣-subunit do not contribute to the difference in light sensitivity between rods and cones (but see Chen et al, 2010).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…One of the key unresolved questions is how the physiological differences between rods and cones can be correlated with the distinctive properties of their phototransduction proteins. Previous studies have shown that the lower thermal stability of cone pigments is likely to contribute to the lower sensitivity of cones but, once activated, rod and cone pigments can couple equally efficiently to rod or cone transducin (Kefalov et al, 2003(Kefalov et al, , 2005Shi et al, 2005Shi et al, , 2007Fu et al, 2008). Thus, consistent with our previous research (Deng et al, 2009) and other studies (Ma et al, 2001), the signaling properties of rod and cone transducin ␣-subunit do not contribute to the difference in light sensitivity between rods and cones (but see Chen et al, 2010).…”
Section: Introductionsupporting
confidence: 81%
“…Previous studies have shown that the lower thermal stability of cone pigments is likely to contribute to the lower sensitivity of cones but, once activated, rod and cone pigments can couple equally efficiently to rod or cone transducin (Kefalov et al, 2003(Kefalov et al, , 2005Shi et al, 2005Shi et al, , 2007Fu et al, 2008). Thus, consistent with our previous research (Deng et al, 2009) and other studies (Ma et al, 2001), the signaling properties of rod and cone transducin ␣-subunit do not contribute to the difference in light sensitivity between rods and cones (but see Chen et al, 2010). As a result, the expression levels and molecular properties of phototransduction components downstream of transducin are likely to play an important role in defining the distinctive physiological properties of rods and cones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in an unstable protein and leads to degeneration of photoreceptor cells (21). Lack of a functional heterologous expression system and suitable animal models has hampered the in-depth analysis needed to understand the role of postprenylation processing in PDE6 function (22).The role of prenylation and methyl esterification of proteins in the maintenance of retinal neurons has been investigated by injecting lovastatin, an inhibitor of HMG-CoA reductase, and Nacetyl-S-farnesyl-L-cysteine, an inhibitor of ICMT, into the eye (23). After 4 d, the retinas were severely disorganized and formed rosette-like structures (23).…”
mentioning
confidence: 99%
“…This results in an unstable protein and leads to degeneration of photoreceptor cells (21). Lack of a functional heterologous expression system and suitable animal models has hampered the in-depth analysis needed to understand the role of postprenylation processing in PDE6 function (22).…”
mentioning
confidence: 99%